2014
DOI: 10.3766/jaaa.25.10.2
|View full text |Cite
|
Sign up to set email alerts
|

Tympanometry Screening Criteria in Children Ages 5–7 Yr

Abstract: An 80% reduction in tympanometry referrals for children ages 6 and 7 yr compared with children age 5 yr argues for tympanometry as a first-tier screening method in older children only. The impact of regional seasonal influences, representing an increase in referrals as high as 3.5 times from one month to another, should also inform and direct pediatric screening programs for middle-ear functioning and/or hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Middle ear effusion is more common in younger children [3] and [29] and may explain the higher prevalence rate of hearing loss in the youngest population of this study (4.9%). One in three conductive hearing losses presented with type B tympanogram and minimal wax.…”
Section: Discussionmentioning
confidence: 69%
“…Middle ear effusion is more common in younger children [3] and [29] and may explain the higher prevalence rate of hearing loss in the youngest population of this study (4.9%). One in three conductive hearing losses presented with type B tympanogram and minimal wax.…”
Section: Discussionmentioning
confidence: 69%
“…A study by Sideris and Glattke [28] found that children younger than four years were often unable to perform pure tone screening, suggesting that pure tone audiometry requires a higher level of cognitive maturity. Additionally, the incidence of acute otitis media and otitis media with effusion is high in LMICs, with a higher incidence in children between the ages of two and five years, thus adding to a higher referral rate [3032]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of this review indicate that school hearing screening is a potentially valuable public health intervention that should be further considered, lending support to the current literature surrounding the benefits of childhood hearing screening after the newborn period, including recommendations from the WHO. 5,12,[37][38][39] However, the substantial variability found in the existing literature base plays a key role in the interpretation of results. Screening test accuracy has a notable impact on assumptions in cost-effectiveness models and can be highly dependent on many factors, such as the level of ambient noise, screening referral thresholds, combination of tests administered, and rescreening protocol.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…15,16,23,38 False positives due to varying amounts of ambient noise, differing frequency and intensity thresholds for referral, and the combination of tympanometry, otoscopy, and otoacoustic emission testing have all been shown to affect overall screening sensitivity and specificity. 12,16,23,38 Moreover, when a child is referred upon initial screening, rescreening is a valuable step in the protocol, reducing the amount of false-positive referrals for further audiometric assessment. 14,16 The sources from which studies based their probability and utility assumptions are important to examine.…”
Section: Summary Of Evidencementioning
confidence: 99%